Influence of geothermal environment on the corrosion fatigue behaviour of standard duplex stainless steel X2CrNiMoN22-5-3. (December 2019) - Wolf, Marcus; Pfennig, Anja
Abstract: In the geothermal environment corrosion fatigue may severely lower the lifetime expectancy of high alloyed steels. Therefore, the corrosion fatigue (CF) of duplex stainless steel X2CrNiMoN22-5-3 was investigated in the Northern German Basin electrolyte at 369 K using a specifically designed corrosion chamber. Although the failure mechanism is independent of surface roughness (low scatter ranges technical surface: TN=1:1.35, polished surface: TN=1.1.95), the life expectancy in purely alternating axial cyclic load to failure was clearly related to surface finish and applied stress amplitude. Specimen with technical surfaces tested at high stress amplitudes (>275 MPa) lasted longer (cycles to failure: P50% at Sa 300 MPa=5x10 5 ) than specimen with polished surfaces (cycles to failure: P50% at Sa 300 MPa=1.5x10 5 ). When applying a protective potential a significant increase of CF life range from 4.7 x 10 5 (free corrosion potential) to 10 7 cycles (potential range from USHE = –450 to – 900 mV) was observed. Microstructural analysis of the CF damage revealed horizontal grain attack within corrosion pit cavities, multiple fatigue cracks and preferable deterioration of austenitic phase. At low stress pitting is the initiating crack growth process whereas at high stress amplitudes the formation of micro cracks is reason for crack propagation and failure.